Women trauma survivors of the Rwandan genocide: A seven week group building exercise - Jacinto, George A; Chapple, Reshawna L; Nyiransekuye, Hadidja; Molina, Olga (Groupwork, 2017)
The article highlights the need for a support community group for women who survived the Rwandan Genocide, and who are completing groupwork for Post traumatic Stress Disorder. The authors review practice literature, discuss specific strategies for adult women, many of whom had been children during the genocide, and introduce a seven-week group experience that leads to development of a community of survivors. The seven-week group incorporates a Rites of Passage in association with a spirituality framework. The authors incorporate Rwandan cultural practices familiar to women who had lived in the country prior to the genocide. Keywords: groupwork; group work; trauma; Rwandan genocide; PTSD; survivors; women